O comunismo dos imigrantes armênios de São Paulo (1935-1969) - Loureiro, Heitor de Andrade Carvalho (2012)
This paper investigates the Armenian Communism in São Paulo between 1935 and 1969 and the surveillance and repression of Delegacia Especializada de Ordem Política e Social (DEOPS/SP). Thus, it is analyzed how the Armenians escaped from the Ottoman Empire and how they came to São Paulo. Their passages through Syria and Lebanon, where they rebuilt their lives and society after the Genocide started in 1915, are also observed. It is also discussed how the Armenians were embedded in São Paulo society and economy establishing their own institutions over the years. Finally, it is examined how Communism was developed into the Armenian Community in São Paulo, in opposition to other political groups who had different views on the Armenian recent history and Diaspora organizations. Therefore, it is observed the paths of Levon Yacubian and Jacob Bazarian, in charge of associations and press like Ararat - a voz do povo armênio , a newspaper which was confiscated and investigated by Political Police under the charge of subversion. The criminal records of DEOPS/SP are the main sources of this research, as well as the community press that were not captured by police authorities. Through these documents it is possible to restore the action of the Armenians who supported Communism as a way to support Soviet Armenia